Data Resource Profile: Education and Health Data in New Zealand’s Integrated Data Infrastructure - Schober, Thomas; Bowden, Nicholas; D'Souza, Stephanie; Gibb, Sheree; Milne, Barry; Meehan, Lisa (International Journal of Population Data Science, 2026)
This paper provides an overview of education and health data in New Zealand's Integrated Data Infrastructure (IDI). The IDI combines population-wide administrative, census, and survey data from government agencies and other organisations, enabling detailed research into the interplay between education and health at the individual level. We describe the structure of the IDI, key data sources in education and health, and provide an overview of access procedures and practical considerations for working with the data.